The Role of Accounting in the Design of CEO Equity Compensation - Carter, Mary Ellen; Lynch, Luann J.; Tuna, I˙rem (The Accounting Review, 2007)
We examine the role of accounting in CEO equity compensation design. For a sample of ExecuComp firms in 1995–2001, we find that financial reporting concerns are positively related to stock option use and total compensation, and negatively related to the use of restricted stock. We confirm our findings by examining changes in CEO compensation in firms that begin expensing options in 2002 or 2003. We find that these firms reduce their option use and increase their restricted stock use after starting to expense options but exhibit no decrease in total compensation. Taken together, our analyses suggest that favorable accounting treatment for options led to a higher use of options and lower use of restricted stock than would have been the case absent accounting considerations.